Empowering Muslim students in India: exploring entrepreneurial intentions and venture creation in disadvantaged communities - Mohd Israil, Khaliq Ahmad; Talha, Mohd; Faisal, Syed Mohammad; Khan, Mohd Saaem; Arafat, Mohd Yasir (World Academy of Islamic Management, 2024)
This research is to check whether the models of EI (Entrepreneurial Intention) explain the entrepreneurial phenomenon when applied to Indian Muslims. The framework tested here is Ajzen’s theory of planned behaviour (TPB) and the data has been collected by administering questionnaire among the students at Aligarh Muslim University, Aligarh, India. The study uses a linear regression model to examine the drivers of EI based on TPB. The results partly back the TPB since its construct social norms (SN) found to be insignificant in forecasting EI. Furthermore, highest variance is explained by PBC indicating India’s environment to be less conducive for entrepreneurs than other countries. This study is one of its kind studying Entrepreneurial Intention Models based on TPB framework covering students from Muslim community of India. Additionally, this study also focuses on checking the strength of the TPB in explaining EI among Indian Muslims.